Pengaruh Servant Leadership, Organizational Citizenship Behavior, Kecocokan Orang-Organisasi serta Identifikasi Organisasi (Studi Pada Organisasi Kemahasiswaan di Lingkungan Universitas Kristen Maranatha) - Meily Margaretha; Yanuar Aditia Prasetio (Jurnal Manajemen Maranatha, 2012)
The objective of this research was to test the relationship and influence of servant leadership towards managerial implicationorganizational citizenship behavior and the person-organization fit and organization identification moderate the relationship with 161 students who have joined organization in Maranatha Christian University, as the respondent. From three hypotheses tested in this research, the entire hypotheses were supported; servant leadership behavior predicts organizational citizenship behavior the person-organization fit and organization identification moderate the relationship between servant leadership and organizational citizenship behavior. One managerial implication that can be applied in this research is leaders who want encourage citizenship behavior among employees would do well to model those behavior towards others.